Grain-size composition predicting models after explosion in open-pit mining - A K Kirsanov; S A Vokhmin; G S Kurchin; E V Zaitseva; E P Volkov (Brawijaya University, 2019)
One of the main technological tasks facing mining engineers today is a reduction of the oversized fraction output. Currently, the efforts of scientists are aimed atdeveloping reliable grain-size composition predicting models for the extracting rock mass, as one of the initial factors for reducing economic losses throughout the technological cycle. However, many of the existing models do not consider the mutual influence of a number of factors, which explains the instability of the drilling and blasting performance indicators, their low efficiency and, as a result, an increased oversized fraction output. The model for grain-size composition predicting for mining enterprises will be interesting only if the proposed technological solution together with a pre-established fraction of rock mass will increase the efficiency of blasting operations with the desired reduction of all material and non-material expenditures. In this paper the authors give a brief overview of the global mining volumes; provides information on the extraction of key types of minerals, as well as revenues derived from their sale. They also specify the direction for future actions in creating a predicting model for the rock mass output of a certain fragmentation after the explosion.